Peripheral Neuropathy in the Lower Limbs of Individuals With Spinal Cord Injury or Disease: A Retrospective Study. (January 2021) - Liang, Jason; Furlan, Julio C.
Abstract : Purpose: This study investigated the frequency and types of peripheral neuropathy in the lower limbs of patients undergoing rehabilitation after traumatic spinal cord injury or spinal cord disease. Methods: This study included consecutive patients with spinal cord injury/spinal cord disease who had electrophysiological assessments during their admission in a rehabilitation center from October 2015 to July 2019. Patients with traumatic spinal cord injury were compared with patients with nontraumatic spinal cord disease. Results: There were 67 patients (52 male patients, 15 female patients; mean age = 56.5 yrs) of whom 36 patients had spinal cord injury and 31 patients had spinal cord disease. Most of the patients were middle-aged men with at least one preexisting medical comorbidity, who were mostly admitted for rehabilitation of cervical, incomplete spinal cord injury/spinal cord disease. Most patients (86.6%) had abnormal electrophysiological studies representing 5.57% of all admissions. A length-dependent polyneuropathy was diagnosed in 0.77% of all admissions ( n = 8). The group of patients with spinal cord injury was comparable with the group of patients with spinal cord disease regarding the other baseline data, clinical, and electrophysiological findings. Conclusions: Diseases of the peripheral nervous system were similarly found among patients undergoing rehabilitation for either spinal cord injury or spinal cord disease. A length-dependent polyneuropathy was diagnosed in 0.77% of all admissions. Timely diagnosis and proper treatment of the cause of peripheral neuropathies in the lower limbs in these patients may potentially influence rehabilitation protocols and improve patient outcomes. Abstract : Abnormal electrophysiological findings were common among patients with either spinal cord injury or disease. Abnormal electrophysiological studies were found in 5.57% of all admissions. Routine electrophysiological assessments could be beneficial in the rehabilitation setting.Supplemental digital content is available in the text.